Partners in prevention : revitalising health and safety in the workplace (London, 2000)
"Revitalising health and safety through workplace partnerships between unions and employers leads to better health and safety measures to protect workers. Case studies illustrate how some of Britain’s best known enterprises are tackling the safety agenda."